Micropsectra sofiae Stur & Ekrem, 2006 (Diptera, Chironomidae) redescribed (Bollettino di zoologia agraria e bachicoltura, 2024)
The examination of adult males and pupal exuviae collected in Italian waters belonging to the genus Micropsectra Kieffer, 1909 allowed to discover the presence of Micropsectra sofiae Stur & Ekrem, 2006 in the Italian Alps. The species cannot be identified using the published keys, so it is redescribed on the basis of adult males, pharate adults and pupal exuviae. M. sofiae belongs to the atrofasciata group and is characterized in the adult male by low AR, long digitus of superior volsella projecting beyond medial margin of setiger, median volsella extending beyond caudal margin of superior volsella; in the pupal stage it is characterizedby the presence of point patches on pleura, of strong points on tergites IV and V lateral to the longitudinal rows of spines. The relations with other species within the Micropsectra atrofasciata group are discussed and the dichotomous key given by Stur & Ekrem (2006) is emended. The distribution of the species is restricted to glacial streams and cold springs and can be considered at risk of extinction due to global climatic change.
Keywords: global change; Microspectra atrofasciata group; morphology; Tanytarsini